Thigh loaded wearable resistance increases sagittal plane rotational work of the thigh resulting in slower 50-m sprint times. Issue 10 (26th November 2022) - Macadam, Paul; Cronin, John B.; Uthoff, Aaron M.; Nagahara, Ryu; Zois, James; Diewald, Shelley; Tinwala, Farhan; Neville, Jono
ABSTRACT: This study determined the acute changes in rotational work with thigh attached wearable resistance (WR) of 2% body mass during 50-m sprint-running. Fourteen athletes completed sprints with, and without, WR in a randomised order. Sprint times were measured via timing gates at 10-m and 50-m. Rotational kinematics were obtained over three phases (steps 1–2, 3–6 and 7–10) via inertial measurement unit attached to the left thigh. Quantification of thigh angular displacement and peak thigh angular velocity was subsequently derived to measure rotational work. The WR condition was found to increase sprint times at 10-m (1.4%, effect size [ES] 0.38, p 0.06) and 50-m (1.9%, ES 0.55, p 0.04). The WR condition resulted in trivial to small increases in angular displacement of the thigh during all phases (0.6–3.4%, ES 0.04–0.26, p 0.09–0.91). A significant decrease in angular velocity of the thigh was found in all step phases (−2.5% to −8.0%, ES 0.17–0.51, p < 0.001–0.04), except extension in step phase 1 with the WR. Rotational work was increased (9.8–18.8%, ES 0.35–0.53, p < 0.001) with WR in all phases of the sprint. Thigh attached WR provides a means to significantly increase rotational work specific to sprinting.